PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI KELURAHAN KHAIRIAH MANDAH KABUPATEN INDRAGIRI HILIR - jurnalmap map (MAP (Jurnal Manajemen dan Administrasi Publik), 2022)
The purpose of this research is to describe the Community Participation in Development in Khairiah Mandah Village, Indragiri Hilir Regency. The results showed that community participation in development generally colored the community to participate in development. If the participation is ideally classified, there are four aspects which are the ideal form of community participation in the Khairiah Mandah Kelurahan Indragiri Hilir Regency in development, namely participation in the form of ideas / thoughts (non-physical), money (funds), material (goods), and direct participation (energy / physical). Channeling ideas and contributing ideas can be channeled through existing formal institutions. Participation in the form of money donations is the participation of community members who voluntarily contribute money for development. Participation in the form of goods is carried out directly which is used for physical development. Participation in the form of personnel referred to here is how the community is involved directly or physically in the implementation of development. This is due to differences in abilities, differences between community members with one another.